Shrinkage Analysis of Carbon Micro Structures Derived from SU-8 Photoresist. (27th April 2016) - Natu, Rucha; Islam, Monsur; Martinez-Duarte, Rodrigo
Abstract : We present preliminary results for the analysis of shrinkage of 3D carbon posts obtained by the pyrolysis of SU-8 precursor structures, in a technique known as Carbon MEMS. Though the shrinkage in the carbon structures is highly reproducible, there is a strong dependence of this shrinkage on the initial dimensions of the SU-8 pillars. Our hypothesis is that the shrinkage depends upon the area available for degassing during carbonization. In this work, this idea is used to analyze shrinkage in cylindrical pillars. The results obtained are studied based on the ratio of lateral and top surface area available for degassing and reinforce the hypothesis about the dependence on surface area.